Manajemen Pembelajaran Daring Menggunakan Education Smart Courses - Agustin, Farida; Oganda, Fitra Putri; Lutfiani, Ninda; Harahap, Eka Purnama (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2020)
Increasing developments in the world of education carried out by tertiary and domestic universities increases the number of students. However, this development has not been matched by the equalization of the course digitization system that can form soft skills and hard skills in several universities in Indonesia which results in gaps for lecturers and students who want to form skills in them. Developing a platform by using sophisticated blockchain technology, Education Smart Courses (E-Scores) can overcome the problems in education that provide courses in the form of gamification. Then the method used in this study is the business model method of CANVA and TKT to measure systematically on technological development. The benefits of Education Smart Courses (E-Scores) and Blockchain-based innovations that can be easily accessed by academics and gamification in educational courses, with the hope of becoming more value in prototypes and will be developed to be able to provide better change.